Madu Bayu” Pudding (Honey Spinach for Mothers) to Treat Anemia in Pregnant Women - Anni Suciawati; Ponisem; Euis Karwati; Ria Fitri Yani; Yhona Farty Indra Yani; Desi Nurabani Sari Sandi; Siti Suci Rahayu; Hani, Umu (International Journal of Community Services, 2025)
Based on a preliminary survey on maternal and child health in Cibunar Village taken from the health center report, the number of pregnant women was 124 pregnant women, with 13 pregnant women (11%) experiencing anemia. One alternative that can help increase hemoglobin levels is consuming "Madu Bayu" (Bayam Honey) pudding to overcome anemia in pregnant women which has a composition as a substitute for blood-boosting supplements, the iron contained in spinach is very high at 3.9 mg / 100 grams, calcium, Vitamin A, Vitamin C, Vitamin E, beta-carotene and fiber. Consuming spinach regularly can prevent anemia because it contains high iron. Pupose: This community service aims to empower the community by increasing the knowledge of pregnant women on how to overcome and treat anemia in pregnant women with the alternative of consuming Spinach Honey Pudding. Method: The method used in community service is to provide counseling on how to overcome and treat anemia in pregnant women with the alternative of consuming Spinach Honey Pudding "Madu Bayu" Result : There was an increase in knowledge, before the counseling was given, it was found that the majority of respondents were in the less than good category, namely 12 respondents (60%), becoming good knowledge, namely 7 respondents (40%) after the counseling was given. Conclusion: that there was an increase in participant knowledge as seen from the participants being able to answer questions about how to overcome anemia in pregnant women.